A novel seismic strengthening method of RC columns confined by direct fastening steel plates. (1st September 2020) - Shan, Z.W.; Looi, D.T.W.; Su, R.K.L.
Highlights: New seismic strengthening method of RC columns by direct fastening steel plate is proposed. Robustness of direct-fastened connections during the whole loading process is validated. Effectiveness of the proposed strengthening method is examined. Simplified N-M curves are proposed for the strengthened RC columns. Generalized force-deformation relation are presented. Abstract: Reinforced concrete (RC) columns designed in accordance with older design codes that do not incorporate seismic resistance are prone to brittle failure. These defective columns may lead to the development of a non-ductile column sway mechanism during a strong earthquake. This failure process can be however remedied by strengthening the defective columns. In this study, an innovative strengthening method that uses direct fastening of steel plates is proposed for the seismic strengthening of RC columns. This method allows quick and easy implementation in practice, compared to the use of conventional steel jacketing connected through welding or bolting. The steel plates in the steel encasement can directly increase the axial, flexural and shear strengths. Furthermore, the confinement generated from the steel encasement can enhance the strength and ductility of the concrete core. This paper describes an experimental investigation of strengthened columns under reversed cyclic lateral load together with a constant vertical load and develops a theoretical model to predict the lateral capacity, which provides the basis for conducting the assessment of the generalized force-deformation relation. The experimental results indicate that the new connection method is robust and the strength and deformation of the strengthened columns are significantly improved. Variables such as connection spacing, number of nails, steel plate thickness and axial load ratio can affect the mechanical behavior of the strengthened columns.